A minimalist computational model of slice hippocampal circuitry based on Neuronify for teaching neuroscience - Lucas Longo; Thiago Lima; Maria Clara Bila; João Brogin; Jean Faber (PLoS ONE, 2025)
The hippocampal formation is vital for processing memory, learning, and spatial navigation. Existing methods are obsolete to address new emerging questions as our understanding of hippocampal circuits and its connections advances. Hence, new techniques with an accessible approach for visualizing and understanding its inner connections and circuitry are needed. Research requires a quick update of textbooks and a better integration of new media to facilitate the teaching of these neural structures. For instance, pictures and diagrams are not enough to fully express the structural and functional effects that each neural circuit imparts. Computational models adapted to these diverse contexts might be a possible solution for such challenge. The construction of minimalist computational models can be an excellent alternative in teaching complex dynamics since they reduce the use of animal models, amplify and simplify structural relationships, promote quick and easy visualization, and uncover possible functional and structural interventions with an educational goal. This interactivity is crucial for a better understanding of the causal relationships between nuclei and neural circuits. Conversely, it is important that those models are simple enough so that any student, regardless of their mathematical background, can understand and manipulate features of interest. Further, software packages that do not require programming knowledge for its use are indispensable, even though this limitation also restricts the representations possible for study. Here, we demonstrate the use of Neuronify software, which uses simple functional representations of neurons and circuits. We represent the most important pathways and connections of the hippocampal formation by building an educational and a simplified models that shows the main known relations between the subregions [Cornu Ammonis (CA)1, CA2, CA3, and CA4], afferent and efferent nucleus (dentate gyrus and subiculum), the first also seeking to couple hippocampal neuroarchitecture, with posterior validation of both by application in an educational context.